The Proto-Slavic Acute Accent - Sukač, Roman (Bohemica Olomucensia, 2015)
Apart from the phonemic, morfological and lexical systems, the reconstruction of Proto-Slavic language includes also the reconstruction of the original accentuation. The study discusses the prominent theories that have been designed to reconstruct the form of both acute and circumflex accents in Proto-Slavic and use them to explain phonemic alternation in present Czech.
Keywords: Proto-Slavic accentuation; acute accent; circumflex accent; phonemic alternation